Impact of COVID-19 on mental health of health care workers in Spain: a mix-methods study - J. Ripoll; X. Chela-Alvarez; E. Briones-Vozmediano; M. A. Fiol de-Roque; R. Zamanillo-Campos; I. Ricci-Cabello; J. Llobera; C. Calafat-Villalonga; M. J. Serrano-Ripoll (BMC, 2024)
Abstract Background Spain's lockdown measures couldn't prevent the severe impact of the COVID-19 first wave, leading to high infections, deaths, and strain on healthcare workers (HCWs). This study aimed to explore the mental health impact on HCWs in the Balearic Islands during the initial months of the pandemic, the influencing factors, and the experiences of those in a COVID-19 environment. Methods Using a mixed-methods approach, the study encompassed quantitative and qualitative elements. Cross-sectional survey data from April to June 2020 comprised HCWs who were emailed invitations. The survey covered demographics, work, clinical and COVID-19 variables, along with psychological distress and PTSD symptoms, using validated measures. Additionally, semi-structured interviews with HCWs offered qualitative insights. Results Three hundred thirty-six HCWs averaging 46.8 years, mainly women (79.2%), primarily nurses in primary care with over 10 years of experience. Anxiety symptoms were reported by 28.8%, 65.1% noted worsened sleep quality, and 27.7% increased psychoactive drug usage. Psychological distress affected 55.2%, while 27.9% exhibited PTSD symptoms. Gender, age, experience, COVID-19 patient contact, and workload correlated with distress, PTSD symptoms, sleep quality, and psychoactive drug usage. Interviews uncovered discomfort sources, such as fear of infection and lack of control, leading to coping strategies like information avoidance and seeking support. Limitations Static cross-sectional design, non-probabilistic sample, and telephone interviews affecting non-verbal cues, with interviews conducted during early pandemic lockdown. Conclusions HCWs faced significant psychological distress during the pandemic's first wave, underscoring the necessity for robust support and resources to counteract its impact on mental health.